2004
DOI: 10.2337/diaspect.17.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Family Conflict and Diabetes Management in Youth: Clinical Lessons From Child Development and Diabetes Research

Abstract: In Brief This articles focuses on family conflict and parenting behavior and their link to self-esteem, treatment adherence, and glycemic control in children and adolescents with type 1 diabetes. From the diabetes literature and normal child development research, the concept of “authoritative parenting” seems especially applicable to the coping tasks facing parents and youth around the management of type 1 diabetes. Research on general family conflict, diabetes-specific family conflict, and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 18 publications
2
64
0
Order By: Relevance
“…Although biological and social changes in youths impact glycemic control in direct and in indirect ways (10), the demands of diabetes management can promote negative feelings in family members. Diabetes-specific family conflict is consistently identified as having a negative impact on adherence to diabetes tasks and glycemic outcomes (11)(12)(13) and may arise from either parental perception of inadequate monitoring frequency or the child's inability to achieve or maintain near-normal blood glucose levels. Thus, conflict around BGM, such as parental nagging or criticism, may serve to promote negative feelings in the youth directed at diabetes management tasks and specifically at BGM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although biological and social changes in youths impact glycemic control in direct and in indirect ways (10), the demands of diabetes management can promote negative feelings in family members. Diabetes-specific family conflict is consistently identified as having a negative impact on adherence to diabetes tasks and glycemic outcomes (11)(12)(13) and may arise from either parental perception of inadequate monitoring frequency or the child's inability to achieve or maintain near-normal blood glucose levels. Thus, conflict around BGM, such as parental nagging or criticism, may serve to promote negative feelings in the youth directed at diabetes management tasks and specifically at BGM.…”
mentioning
confidence: 99%
“…Because optimal glycemic control is often the goal for families, failure to meet the target range of blood glucose levels may also serve to promote feelings of disappointment, guilt, or anger in the youth and subsequently modify adherence to BGM. This collection of difficulties resulting from negative feelings about diabetes management may further serve to promote poor adherence (11)(12)(13)) and psychological problems (e.g., depression) (14 -16).…”
mentioning
confidence: 99%
“…As found in previous research (Cohen et al, 2004; Missotten, Luyckx and Seiffge-Krenke, 2013), the current study found that a positive family environment (as described by a sense of cohesion amongst its members) is strongly associated with the young person achieving the most favourable health outcomes. Cohesion is well recognised as a significant influence upon diabetic control (Anderson, Miller, Auslander, et al, 1981;Mackey, Hilliard, Berger, et al, 2011), it is also associated with parental warmth and the child's cooperation with their diabetic management (Anderson, 2004). By contrast, adolescents with suboptimal diabetic control tend to view their families as less cohesive (Zashikhina and Hagglof, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This can be mitigated to some degree by a well organised and effective management regime which produces better glycaemic control, improves adherence to treatment, and thus, results in less family conflict (Anderson, 2004). As the focus of this parental concern and structured management regime, the young person is likely to be receiving a pattern of parenting somewhat different from their peers.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] These positive outcomes are most likely in cohesive families whose members communicate well, agree on individual responsibilities, behave supportively, and solve problems together. [5][6][7] There are many sources of diabetes-related conflict, however. Arguments over food, blood glucose testing, and exercise are the most common.…”
mentioning
confidence: 99%